2015
DOI: 10.1242/jeb.118760
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of cardiac response to thermal acclimation in the eurythermal goby fishGillichthys mirabilis

Abstract: Cardiac function is thought to play a central role in determining thermal optima and tolerance limits in teleost fishes. Investigating proteomic responses to temperature in cardiac tissues may provide insights into mechanisms supporting the thermal plasticity of cardiac function. Here, we utilized a global proteomic analysis to investigate changes in cardiac protein abundance in response to temperature acclimation (transfer from 13°C to 9, 19 and 26°C) in a eurythermal goby, Gillichthys mirabilis. Proteomic da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 95 publications
6
34
0
Order By: Relevance
“…Indeed, the warm-acclimated Biotest fish displayed a lower activity of LDH, PDH, CS, MDH, AAT and CI at almost all assay temperatures. These findings are indicative of a downregulation of aerobic metabolism in the heart and are consistent with previous studies demonstrating a depression of enzymatic thermal sensitivity and a downregulated expression of enzymes governing glycolysis, tricarboxylic acid cycle and mitochondrial respiration following acclimation and adaptation to warmer habitats in fish (Jayasundara et al, 2015;West et al, 1999). This is also in agreement with observed reductions in whole-animal routine oxygen consumption rate, as well as reduced cardiac power output, heart rate and cardiac output, which are indicative of a reduced cardiac oxygen demand in Biotest perch at given test temperatures (Ekström et al, 2016a;Sandblom et al, 2016).…”
Section: Discussion Acute Effects Of Temperature On Metabolism In Thesupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, the warm-acclimated Biotest fish displayed a lower activity of LDH, PDH, CS, MDH, AAT and CI at almost all assay temperatures. These findings are indicative of a downregulation of aerobic metabolism in the heart and are consistent with previous studies demonstrating a depression of enzymatic thermal sensitivity and a downregulated expression of enzymes governing glycolysis, tricarboxylic acid cycle and mitochondrial respiration following acclimation and adaptation to warmer habitats in fish (Jayasundara et al, 2015;West et al, 1999). This is also in agreement with observed reductions in whole-animal routine oxygen consumption rate, as well as reduced cardiac power output, heart rate and cardiac output, which are indicative of a reduced cardiac oxygen demand in Biotest perch at given test temperatures (Ekström et al, 2016a;Sandblom et al, 2016).…”
Section: Discussion Acute Effects Of Temperature On Metabolism In Thesupporting
confidence: 92%
“…In addition, the transcription of enzymes governing cardiac glycolytic, tricarboxylic acid and oxidative metabolic pathways increased following warm acclimation from 13 to 19°C, but declined at higher acclimation temperatures in the eurythermal goby species Gillichthys mirabilis. Furthermore, warm acclimation resulted in downregulated expression of hydroxyacyl-coenzyme A dehydrogenase (HOAD), indicating a reduced fatty acid oxidative capacity, whilst lactate dehydrogenase (LDH) transcription was elevated, indicating a potential increased importance of anaerobic metabolism at high temperatures in these fish (Jayasundara et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…GAA might be able to support creatine production and increase CK activity. In the present study, the increased level of circulating CK indicates the previously reported potential role in maintaining high ATP turnover at low temperature (Jayasundara et al 2015). Similar to this study, a significant increase in CK activity was seen in the group supplemented with creatine (Dobgenski et al 2016).…”
Section: Blood Biochemical and Haematological Parameterssupporting
confidence: 91%
“…Moreover, due to the complexity of the thermal acclimation process, the different components of mitochondrial metabolism affected by temperature are not clear, as they may depend on the time course and the intensity of the thermal exposure (Hazel, 1972(Hazel, , 1995Sidell, 1983;Blier and Guderley, 1993;St-Pierre et al, 1998;Guderley, 2004;Itoi et al, 2003;Kraffe et al, 2007;Iftikar et al, 2014;Jayasundara et al, 2015). For example, in isolated mitochondria from the red muscle of rainbow trout, Oncorhynchus mykiss, a temperature increase from 5 to 9°C over 2 days (Bouchard and Guderley, 2003) or from 5 to 15°C over 3 days (Kraffe et al, 2007) did not significantly change rates of pyruvate oxidation (state 3 and state 4; oxygen consumption in presence and absence of ADP, respectively, when pyruvate is provided to the mitochondria).…”
Section: Introductionmentioning
confidence: 99%